THE INFLUENCE OF TAX KNOWLEDGE AND TAX AUDITS ON INDIVIDUAL TAXPAYER COMPLIANCE - Ni Komang Priyahita; I Ketut Sujana (Adisam Publisher, 2025)
Compliance of Individual Taxpayers (WPOP) is a crucial aspect in optimizing state revenue through the taxation sector. The low level of individual taxpayer compliance at the Singaraja Primary Tax Office (KPP Pratama Singaraja), which ranks fourth lowest in the Bali region, highlights the need to evaluate the influencing factors. This study aims to analyze the effect of tax knowledge and tax audits on individual taxpayer compliance. Data were obtained through a survey of 100 taxpayers selected using purposive sampling and analyzed using multiple linear regression analysis. The results show that tax knowledge and tax audits have a positive and significant effect on individual taxpayer compliance. These findings underscore the importance of improving taxpayer education and fiscal supervision to encourage more optimal tax compliance.